Ultra-black light-absorbing coating based on laser etching and preparation method thereof
Through the preparation method based on laser etching, the laser power and scanning rate are adjusted to remove the pure resin film on the surface of carbon nanotubes, the problem of difficulty in preparing ultra-black light absorption coatings in the prior art is solved, and the coating preparation with high efficiency and excellent performance is achieved.
Patent Information
- Application Number
- CN202410761974.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-06-13
AI Technical Summary
The prior art is difficult to effectively prepare ultra-black light absorption coatings, and the preparation steps are cumbersome, so the obtained product is not ideal.
Using a preparation method based on laser etching, the pure resin film on the surface of the carbon nanotube is removed by adjusting the relationship between laser power and scanning rate, and the porous microstructure of the carbon nanotube is exposed, thereby improving the light absorption performance of the coating.
It realizes efficient acquisition of ultra-black light absorption coating, improves the light absorption performance of the coating, and solves the problems of high production cost and low production efficiency in the prior art.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of light absorbing coatings, and in particular to an ultra-black light absorbing coating based on laser etching and a preparation method thereof. Background Art
[0002] Ultra-black light-absorbing coatings can improve the sensitivity of optical instruments and can be used for astronomical cameras, telescopes, and infrared scanning systems. They can also be used in optical components and light baffles, sun hoods, inner walls of lens barrels, darkrooms, and other systems and parts that need to eliminate stray light to improve the accuracy of optical devices. They also have broad application prospects in space exploration, precision instruments, ultra-darkrooms, and photovoltaic modules. At the same time, ultra-black materials are close to pure black, which brings more possibilities to the field of visual arts.
[0003] In recent years, researchers have used advanced technologies such as atomic layer deposition or chemical vapor deposition to prepare a carbon nanotube forest structure with multiple scattering characteristics on aluminum foil, achieving an absorbance of 99.96%, which was named "Vantablack" and has very important significance in fields such as astronomy and military. However, this method has high preparation costs, low production efficiency, and strict requirements on the growth environment and post-maintenance, and cannot meet the requirements of practical applications.
[0004] The light-absorbing coatings that can be mass-produced by spraying on the market are all based on organic resins as adhesives to bond light-absorbing materials (such as carbon nanotubes). However, due to the existence of surface tension during the cross-linking and curing process, the organic resin will coat the carbon nanotubes on the coating surface to form a layer of pure resin film, which increases the refractive index difference between the light and the coating surface and weakens the light-absorbing performance. Removing the pure resin film on the surface of the carbon nanotubes is conducive to reducing the refractive index of the light-absorbing coating and improving the light absorption rate. The removal methods for the resin film generally include chemical methods and plasma etching methods. The chemical method has low controllability and cannot selectively corrode the pure resin film, making it difficult to achieve the effect of reducing the refractive index of the light-absorbing coating. The plasma etching method has complicated steps and cannot obtain an ideal ultra-black light-absorbing coating.
[0005] Laser etching is expected to achieve efficient removal of pure resin film on the surface of carbon nanotubes, and obtain ultra-black light absorbing coatings with excellent performance. However, during laser etching, the laser power and scanning rate have a great influence on the absorbance of the absorbing coating. It is difficult to obtain an ultra-black light absorbing coating by arbitrarily setting the laser power and scanning rate. Therefore, how to provide an ultra-black light absorbing coating based on laser etching and a preparation method thereof, and how to improve the absorbance of the ultra-black light absorbing coating by adjusting the relationship between laser power and scanning rate is a difficult problem to be solved in this field. Summary of the invention
[0006] In view of this, the present invention provides an ultra-black light absorbing coating based on laser etching and a preparation method thereof, so as to solve the problems that the existing method cannot successfully prepare the ultra-black light absorbing coating, and the preparation steps are cumbersome and the obtained product is not ideal.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing an ultra-black light-absorbing coating based on laser etching comprises the following steps:
[0009] 1) mixing chlorinated polypropylene / acrylic acid copolymer, water-based acrylic resin, ethanol, water, carbon nanotube dispersant, defoamer and carbon nanotubes to obtain a mixed slurry;
[0010] 2) coating the mixed slurry on a substrate and performing laser etching to obtain an ultra-black light-absorbing coating;
[0011] The reflectivity Z% of the ultra-black light absorbing coating satisfies the following relationship with the scanning rate x and laser power y in laser etching:
[0012] Z=(Z 0 +A 01 *x+B 01 *y+B 02 *y 2 +C 02 *x*y) / (1+A 1 *x+A 2 *x 2 +B 1 *y+B 2 *y 2 +C 2 *x*y), where Z 0 is -2255.28249, A 01 is 3.00661, B 01 is 109.5623, B 02 is -0.44267, C 02 is -0.09549, A 1 is -4.89699, A 2 is 0.00578, B 1 is 252.51703, B 2 is -7.10883, C 2 is -0.11944; the value range of x is 700~1000mm / s, and the value range of y is 5.4~12.6W.
[0013] Preferably, the mass ratio of the chlorinated polypropylene / acrylic acid copolymer, the water-based acrylic resin, ethanol, water, the carbon nanotube dispersant, the defoaming agent and the carbon nanotubes is 1-2:10-12:15-20:25-30:2-4:0.1-0.3:2-4.
[0014] Preferably, the mixing in step 1) is grinding mixing, the grinding mixing rate is 1000-3000 rpm, and the grinding mixing time is 10-14 hours.
[0015] Preferably, the substrate in step 2) further comprises a pretreatment step, wherein the pretreatment step is to rub the substrate to generate scratches on the surface of the substrate.
[0016] Preferably, the coating in step 2) includes multiple coatings, the number of coatings is 8 to 12 times, and the speed of each coating is 8 to 12 mL / min.
[0017] Preferably, after the coating in step 2) is completed, a polymerization step is also included.
[0018] Preferably, the temperature of the polymerization step is 50-80° C., and the time of the polymerization step is 10-14 hours.
[0019] Preferably, the parameters of the laser etching are set as follows: the wavelength of the laser etching is 9.23-9.31 µm, and the diameter of the laser spot is 60-80 µm.
[0020] Another object of the present invention is to provide an ultra-black light absorbing coating prepared by the above preparation method.
[0021] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0022] In traditional light-absorbing coatings, due to the action of surface tension, the resin material used as a binder during the spraying process usually forms a resin film on the surface to cover the carbon nanotubes. At this time, the light contact interface is an air / resin interface, and the existence of this interface seriously affects the light absorption performance of the coating. The present invention is based on laser etching technology, which removes the surface resin layer to expose the porous microstructure of carbon nanotubes overlapping each other, converts the air / resin light contact interface into an air / carbon nanotube light contact interface, and greatly improves the light absorption performance of the coating. The laser power and the laser scanning rate are the core parameters that affect the laser etching depth. The relationship between the two directly affects the light absorption performance of the coating after etching. The present invention provides a formula for the relationship between the laser power and the laser scanning rate parameters and the light absorption performance of the coating, which can efficiently obtain an ultra-black light-absorbing coating and improve the light absorption performance of the coating. DETAILED DESCRIPTION
[0023] The present invention provides a method for preparing an ultra-black light absorbing coating based on laser etching, comprising the following steps:
[0024] 1) mixing chlorinated polypropylene / acrylic acid copolymer, water-based acrylic resin, ethanol, water, carbon nanotube dispersant, defoamer and carbon nanotubes to obtain a mixed slurry;
[0025] 2) coating the mixed slurry on a substrate and performing laser etching to obtain an ultra-black light-absorbing coating;
[0026] The reflectivity Z% of the ultra-black light absorbing coating satisfies the following relationship with the scanning rate x and laser power y in laser etching:
[0027] Z=(Z 0 +A 01 *x+B 01 *y+B 02 *y 2 +C 02 *x*y) / (1+A 1 *x+A 2 *x 2 +B 1 *y+B 2 *y 2 +C 2 *x*y), where Z 0 is -2255.28249, A 01 is 3.00661, B 01 is 109.5623, B 02 is -0.44267, C 02 is -0.09549, A 1 is -4.89699, A 2 is 0.00578, B 1 is 252.51703, B 2 is -7.10883, C 2 is -0.11944; the value range of x is 700~1000mm / s, and the value range of y is 5.4~12.6W.
[0028] In the present invention, the mass ratio of the chlorinated polypropylene / acrylic acid copolymer, water-based acrylic resin, ethanol, water, carbon nanotube dispersant, defoaming agent and carbon nanotubes is 1-2:10-12:15-20:25-30:2-4:0.1-0.3:2-4; preferably 1.2-1.8:10.5-11.5:16-18:26-30:2.5-3.5:0.1-0.3:2-4; further preferably 1.35:11:18:29.8:3:0.2:3.
[0029] In the present invention, the mixing in step 1) is grinding mixing, and the grinding mixing rate is 1000-3000 rpm, specifically 1200 rpm, 1500 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2500 rpm, 2800 rpm; the grinding mixing time is 10-14 h, specifically 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h.
[0030] In the present invention, the substrate in step 2) further comprises a pretreatment step, wherein the pretreatment step is to rub the substrate to generate scratches on the surface of the substrate.
[0031] In the present invention, the substrate is preferably an aluminum substrate.
[0032] In the present invention, the coating in step 2) includes multiple coatings, the number of coatings is 8 to 12 times, specifically 9 times, 10 times, and 11 times; the speed of each coating is 8 to 12 mL / min, specifically 9 mL / min, 10 mL / min, and 11 mL / min.
[0033] In the present invention, after the coating in step 2) is completed, a polymerization step is also included.
[0034] In the present invention, the temperature of the polymerization step is 50-80°C, specifically 55°C, 60°C, 65°C, 70°C, 75°C; the time of the polymerization step is 10-14h, specifically 11h, 12h, 13h.
[0035] In the present invention, the polymerization step is preferably carried out in a constant temperature drying oven.
[0036] In the present invention, the parameters of the laser etching are set as follows: the wavelength of the laser etching is 9.23~9.31µm, specifically 9.25µm, 9.26µm, 9.28µm, 9.30µm; the laser spot diameter is 60~80µm, specifically 62µm, 65µm, 68µm, 70µm, 72µm, 75µm, 78µm.
[0037] The present invention also provides an ultra-black light absorbing coating prepared by the above preparation method.
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0039] 1.35 parts of chlorinated polypropylene / acrylic acid copolymer (EV emulsion, Guangzhou Houhuan Chemical Additive Co., Ltd.), 11 parts of water-based acrylic resin (HR-005, Guangzhou Houhuan Chemical Additive Co., Ltd.), 18 parts of ethanol, 29.8 parts of water, 3 parts of carbon nanotube dispersant (HH-2190, Guangzhou Houhuan Chemical Additive Co., Ltd.), 0.2 parts of defoamer (AD20, Guangzhou Houhuan Chemical Additive Co., Ltd.) and 3 parts of carbon nanotubes (15 μm, Shanghai Yaotian New Material Technology Co., Ltd.) were mixed, placed in a basket mill equipped with zirconia balls and ground at a speed of 2000 rpm for 12 h to obtain a mixed slurry;
[0040] The aluminum substrate was rubbed with sandpaper until uniform scratches covered the entire surface, and then the slurry was sprayed on the surface of the aluminum substrate at a spraying rate of 10 mL / min. After drying, it was sprayed again, and the spraying was repeated 9 times, and then placed in a constant temperature drying oven and polymerized at 60°C for 12 hours. After the polymerization, the coating was treated with laser etching to obtain an ultra-black light absorbing coating; wherein the laser etching parameters are as follows: the laser scanning rate is 700 mm / s, the laser power is 9 W, the laser wavelength is 9.3 μm, and the laser spot diameter is 70 μm. According to the relationship, the laser scanning rate x is set to 700 mm / s, and the laser power y is set to 9 W; the theoretical reflectivity is 0.57%.
[0041] According to actual detection by an ultraviolet / visible / near infrared spectrophotometer, the actual reflectivity of the ultra-black light absorbing coating obtained in this embodiment is 0.50%.
[0042] The relationship is as follows:
[0043] Z=(Z 0 +A 01 *x+B 01 *y+B 02 *y 2 +C 02 *x*y) / (1+A 1 *x+A 2 *x 2 +B 1 *y+B 2 *y 2 +C 2 *x*y), where Z 0 is -2255.28249, A 01 is 3.00661, B 01 is 109.5623, B 02 is -0.44267, C 02 is -0.09549, A 1 is -4.89699, A 2 is 0.00578, B 1is 252.51703, B 2 is -7.10883, C 2 It is -0.11944. Example 2
[0044] The difference between this embodiment and embodiment 1 lies in the different laser etching parameters. The specific laser etching parameters are as follows: the laser scanning rate is 900 mm / s, the laser power is 7.2 W, the laser wavelength is 9.3 μm, the laser spot diameter is 70 μm, and the laser scanning rate x is set to 900 mm / s and the laser power y is set to 7.2 W according to the relationship; the theoretical reflectivity is 0.63%.
[0045] According to actual detection by an ultraviolet / visible / near infrared spectrophotometer, the actual reflectivity of the ultra-black light absorbing coating obtained in this embodiment is 0.6%. Example 3
[0046] The difference between this embodiment and embodiment 1 lies in the different laser etching parameters. The specific laser etching parameters are as follows: the laser scanning rate is 1000 mm / s, the laser power is 5.4 W, the laser wavelength is 9.3 μm, the laser spot diameter is 63 μm, and the laser scanning rate x is set to 1000 mm / s and the laser power y is set to 5.4 W according to the relationship; the theoretical reflectivity is 0.58%.
[0047] According to actual detection by an ultraviolet / visible / near infrared spectrophotometer, the actual reflectivity of the ultra-black light absorbing coating obtained in this embodiment is 0.61%. Example 4
[0048] 1 part of chlorinated polypropylene / acrylic acid copolymer, 10 parts of water-based acrylic resin, 20 parts of ethanol, 30 parts of water, 4 parts of carbon nanotube dispersant, 0.3 parts of defoamer and 4 parts of carbon nanotubes were mixed, placed in a basket grinder equipped with zirconium oxide balls and ground at a speed of 1500 rpm for 10 hours to obtain a mixed slurry, the components of which were the same as those in Example 1;
[0049] The aluminum substrate was rubbed with sandpaper until uniform scratches covered the entire surface, and then the slurry was sprayed on the surface of the aluminum substrate at a spraying rate of 8 mL / min. After drying, it was sprayed again, and the spraying was repeated 9 times, and then placed in a constant temperature drying oven and polymerized at 60°C for 12 hours. After the polymerization, the coating was treated with laser etching to obtain an ultra-black light absorbing coating; wherein the laser etching parameters are as follows: the laser scanning rate is 1000 mm / s, the laser power is 9 W, the laser wavelength is 9.3 μm, and the laser spot diameter is 63 μm. According to the relationship, the laser scanning rate x is set to 1000 mm / s, and the laser power y is set to 9 W; the theoretical reflectivity is 0.56%.
[0050] According to actual detection by an ultraviolet / visible / near infrared spectrophotometer, the actual reflectivity of the ultra-black light absorbing coating obtained in this embodiment is 0.54%.
[0051] The relationship is as follows:
[0052] Z=(Z 0 +A 01 *x+B 01 *y+B 02 *y 2 +C 02 *x*y) / (1+A 1 *x+A 2 *x 2 +B 1 *y+B 2 *y 2 +C 2 *x*y), where Z 0 is -2255.28249, A 01 is 3.00661, B 01 is 109.5623, B 02 is -0.44267, C 02 is -0.09549, A 1 is -4.89699, A 2 is 0.00578, B 1 is 252.51703, B 2 is -7.10883, C 2 It is -0.11944.
[0053] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0054] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an ultra-black light-absorbing coating based on laser etching, characterized in that: The steps include: 1) mixing chlorinated polypropylene / acrylic acid copolymer, water-based acrylic resin, ethanol, water, carbon nanotube dispersant, defoamer and carbon nanotubes to obtain a mixed slurry; 2) coating the mixed slurry on a substrate and performing laser etching to obtain an ultra-black light-absorbing coating; The parameters of the laser etching are set as follows: The wavelength of laser etching is 9.23~9.31µm, and the laser spot diameter is 60~80µm; The reflectivity Z% of the ultra-black light absorbing coating satisfies the following relationship with the scanning rate x and laser power y in laser etching: Z=(Z0+A 01 *x+B 01 *y+B 02 *y 2 +C 02 *x*y) / (1+A1*x+A2*x 2 +B1*y+B2*y 2 +C2*x*y), where Z0 is -2255.28249, A 01 is 3.00661, B 01 is 109.5623, B 02 is -0.44267, C 02 is -0.09549, A1 is -4.89699, A2 is 0.00578, B1 is 252.51703, B2 is -7.10883, and C2 is -0.11944; the value range of x is 700~1000mm / s, and the value range of y is 5.4~12.6W.
2. The method for preparing an ultra-black light absorbing coating based on laser etching according to claim 1, characterized in that: The mass ratio of the chlorinated polypropylene / acrylic acid copolymer, water-based acrylic resin, ethanol, water, carbon nanotube dispersant, defoamer and carbon nanotube is 1-2:10-12:15-20:25-30:2-4:0.1-0.3:2-4.
3. The method for preparing an ultra-black light absorbing coating based on laser etching according to claim 2, characterized in that: The mixing in step 1) is grinding mixing, the grinding mixing rate is 1000-3000 rpm, and the grinding mixing time is 10-14 hours.
4. The method for preparing an ultra-black light absorbing coating based on laser etching according to any one of claims 1 to 3, characterized in that: The substrate in step 2) further comprises a pretreatment step, wherein the pretreatment step is to rub the substrate to generate scratches on the surface of the substrate.
5. The method for preparing an ultra-black light absorbing coating based on laser etching according to claim 4, characterized in that: The coating in step 2) includes multiple coatings, the number of coatings is 8 to 12 times, and the speed of each coating is 8 to 12 mL / min.
6. The method for preparing an ultra-black light absorbing coating based on laser etching according to claim 5, characterized in that: After the coating in step 2) is completed, a polymerization step is also included.
7. The method for preparing an ultra-black light absorbing coating based on laser etching according to claim 6, characterized in that: The temperature of the polymerization step is 50-80° C., and the time of the polymerization step is 10-14 hours.